Young children’s production of syllable stress: An acoustic analysis - Schwartz, Richard G.; Petinou, Kakia; Goffman, Lisa; Lazowski, Gerri; Cartusciello, Christine (My University, 1996)
The acoustic characteristics of stress were examined in young children’s productions of minimal pairs of novel words ~e.g., sofi versus so’fi!. Fourteen 2-year-olds participated as subjects. Their productions were analyzed in terms of vowel duration, syllable duration, peak amplitude, and peak fundamental frequency. The analyses revealed that children produced stressed and unstressed syllables distinctly along each of the dimensions examined. The absolute and relative ~unstressed/ stressed! values of the children’s productions were compared to those of the single adult experimenter, who modeled the novel words, permitting a unique comparison of input to children’s productions. One systematic difference was the relative values; the children’s stressed and unstressed syllables were less distinct than the adults along each of the acoustic correlates. Furthermore, the acoustic features of both stressed and unstressed syllables appear to be subject to developmental change. The results are discussed in terms of their implications for young children’s production capabilities and for the relationship between input and children’s production characteristics.
Keywords: Child; Preschool; Female; Humans; Infant; Male Speech; Speech Acoustics; Speech Production Measurement